PTEN regulates RPA1 and protects DNA replication forks - Wang, Guangxi; Li, Yang; Wang, Pan; Liang, Hui; Cui, Ming; Zhu, Minglu; Guo, Limei; Su, Qian; Sun, Yujie; McNutt, Michael A; Yin, Yuxin (Cell research, 2015)
Tumor suppressor PTEN regulates cellular activities and controls genome stability through multiple mechanisms. In this study, we report that PTEN is necessary for the protection of DNA replication forks against replication stress. We show that deletion of PTEN leads to replication fork collapse and chromosomal instability upon fork stalling following nucleotide depletion induced by hydroxyurea. PTEN is physically associated with replication protein A 1 （RPA1） via the RPA1 C-terminal domain. STORM and iPOND reveal that PTEN is localized at replication sites and promotes RPA1 accumulation on replication forks. PTEN recruits the deubiquitinase OTUB1 to mediate RPA1 deubiquitination. RPA1 deletion confers a phenotype like that observed in PTEN knockout cells with stalling of rep- lication forks. Expression of PTEN and RPA1 shows strong correlation in colorectal cancer. Heterozygous disruption of RPA1 promotes tumorigenesis in mice. These results demonstrate that PTEN is essential for DNA replication fork protection. We propose that RPA1 is a target of PTEN function in fork protection and that PTEN maintains genome stability through regulation of DNA replication.